Validation of a Swedish version of the Facial Disability Index (FDI) and the Facial Clinimetric Evaluation (FaCE) scale. (June 2013) - Marsk, Elin; Hammarstedt-Nordenvall, Lalle; Engström, Mats; Jonsson, Lars; Hultcrantz, Malou
Abstract Conclusion: Swedish versions of the Facial Disability Index (FDI) and Facial Clinimetric Evaluation (FaCE) scale are psychometrically valid. Both questionnaires can be used for clinical studies on peripheral facial palsy patients, and provide important information on quality of life. Objectives: To translate and validate Swedish versions of the FDI and FaCE scale in patients with peripheral facial palsy. Methods: Translation of the original questionnaires followed international guidelines. Internal consistency and test–retest stability were assessed in adult patients with stable peripheral facial palsy. Facial function was examined with the Sunnybrook and House-Brackmann scales. Subjects answered the questionnaires twice with a 2-week interval. Validity was assessed by comparing FDI and FaCE scale scores to SF-36 and Sunnybrook/House-Brackmann scores. Results: Ninety-three patients were included, 53% women and 47% men, mean age 56.9 years and mean duration of palsy 51.9 months. The questionnaires showed good/excellent psychometric properties with Cronbach's α scores between 0.76 and 0.92. In the test–retest analysis, intra-class correlation coefficients were very good for both questionnaires with scores of 0.83–0.97. Both questionnaires showed good sensitivity to discriminate between patients with varying degrees of facial dysfunction. Moderate to strong correlation was found between the social domains in the questionnaires when compared with the equivalent domains in SF-36.